Dynamic Measurement of Disease Activity in Acute Pancreatitis: The Pancreatitis Activity Scoring System. (July 2017) - Wu, Bechien U; Batech, Michael; Quezada, Michael; Lew, Daniel; Fujikawa, Kelly; Kung, Jonathan; Jamil, Laith H; Chen, Wansu; Afghani, Elham; Reicher, Sonya; Buxbaum, James; Pandol, Stephen J
Abstract : Objectives: Acute pancreatitis has a highly variable course. Currently there is no widely accepted method to measure disease activity in patients hospitalized for acute pancreatitis. We aimed to develop a clinical activity index that incorporates routine clinical parameters to assist in the measurement, study, and management of acute pancreatitis. Methods: We used the UCLA/RAND appropriateness method to identify items for inclusion in the disease activity instrument. We conducted a systematic literature review followed by two sets of iterative modified Delphi meetings including a panel of international experts between November 2014 and November 2015. The final instrument was then applied to patient data obtained from five separate study cohorts across Southern California to assess profiles of disease activity. Results: From a list of 35 items comprising 6 domains, we identified 5 parameters for inclusion in the final weighted clinical activity scoring system: organ failure, systemic inflammatory response syndrome, abdominal pain, requirement for opiates and ability to tolerate oral intake. We applied the weighted scoring system across the 5 study cohorts comprising 3, 123 patients. We identified several distinct patterns of disease activity: (i) overall there was an elevated score at baseline relative to discharge across all study cohorts, (ii) there were distinct patterns of disease activity related to duration of illness as well as (iii) early and persistent elevation of disease activity among patients with severe acute pancreatitis defined as persistent organ failure. Conclusions: We present the development and initial validation of a clinical activity score for real‐time assessment of disease activity in patients with acute pancreatitis.